Does the research reported in mathematics education journals have any relevance for practicing l teachers? - Lester Jr, Frank (NOMAD Nordic Studies in Mathematics Education, 1998)
This paper is a revised and abbreviated version of a paper presented by Frank Lester at the plenary session at the research presession of the annual meeting of the National Council of Teachers of Mathematics in San Diego on April 23, 1996. It is the result of numerous discussions among the author, Gudmundur Birgisson and Paul Kehle over a period of several months beginning in November, 1995. During that time Birgisson and Kehle were doctoral students in the Mathematics Education Program at Indiana University. It has also been presented at the annual conference of the National Association for Research on Teaching Mathematics and Science, Vaasa, Finland in 1998